Groundwater denitrification using electro-assisted autotrophic processes: exploring bacterial community dynamics in a single-chamber reactor - Toledo-Alarcón, Javiera; Ortega-Martinez, Eduardo; Pavez-Jara, Javier; Franchi, Oscar; Nancucheo, Ivan; Zuñiga-Barra, Héctor; Campos, Jose Luis; Jeison, David (Frontiers in Bioengineering and Biotechnology, 2025)
Nitrate, a major groundwater pollutant from anthropogenic activities, poses serious health risks when present in drinking water. Denitrification using bio-electrochemical reactors (BER) offers an innovative technology, eco-friendly solution for nitrate removal from groundwater. BER use electroactive bacteria to reduce inorganic compounds like nitrate and bicarbonate by transferring electrons directly from the cathode. In our work, two batch BER were implemented at 1V and 2V, using anaerobic digestate from a full-scale wastewater treatment plant as inoculum. Nitrate, nitrite, sulfate, total ammoniacal nitrogen, and 16S rRNA analysis of bacterial community, were monitored during BER operation. The results showed effective nitrate removal in all BERs, with denitrification rate at 1V and 2V higher than the Control system, where endogenous respiration drove the process. At 1V, complete nitrate conversion to N2 occurred in 4 days, while at 2V, it took 14 days. The slower rate at 2V was likely due to O2 production from water electrolysis, which competed with nitrate as final electron acceptor. Bacterial community analysis confirmed the electroactive bacteria selection like the genus Desulfosporosinus and Leptolinea, confirming electrons transfer without an electroactive biofilm. Besides, Hydrogenophaga was enhanced at 2V likely due to electrolytically produced H2. Sulfate was not reduced, and total ammoniacal nitrogen remained constant indicating no dissimilatory nitrite reduction of ammonia. These results provide a significant contribution to the scaling up of electro-assisted autotrophic denitrification and its application in groundwater remediation, utilizing a simple reactor configuration-a single-chamber, membrane-free design- and a conventional power source instead of a potentiostat.